Inovasi Bisnis Keripik Pisang: Membangun Ekonomi Desa dengan Ide Kreatif - Citra Oktavina Eka Lidyawati; Febriarsitas Eka Sasmita; Rahayu Mardikaningsih; Fayola Issalillah; Nelud Darajaatul Aliyah; Rafadi Khan Khayru; Didit Darmawan (Jurnal Kajian dan Penelitian Umum, 2024)
The community economy in today's era can develop faster if balanced with innovative and creative ideas. Business is the activity of a person or group of people who create goods or services and exchange them for money for personal gain. The method used in the implementation of this community service is Asset Based Community Development (ABCD) with the banana chips business as an asset that can be developed. This community service aims to describe the idea of a business opportunity for making kripi (banana chips) to improve the community's economy in Becirongengor Village. The results obtained show that making kripi (banana chips) is able to become one of the innovative ideas to improve the economy of the community in Becirongengor Village and will continue to innovate in terms of taste and market expansion.